Pheophorbide A and SN38 conjugated hyaluronan nanoparticles for photodynamic- and cascadic chemotherapy of cancer stem-like ovarian cancer. (1st August 2022) - Lee, Junghan; Davaa, Enkhzaya; Jiang, Yixin; Shin, Kyung-Ju; Kim, Min Hye; An, Hyunsu; Kim, Jinho; Cho, Steve K.; Yang, Su-Geun
Abstract: In this study, we designed photo-triggered reactive oxygen species (ROS)-generating pheophorbide A and ROS-cleavable thioketal-SN38 conjugated hyaluronan-cholesterol nanoparticles (PheoA-SN38-HC NPs). And we observed the combined therapeutic effects of PheoA-SN38-HC NPs against HEY-T30 human ovarian cancer (OC) model. Clinical Proteomic Tumor Analysis Consortium (CPTAC) data showed that the expression of cancer stem cell (CSC) markers (CD44, ALDH1A1, and CD117) is highly associated with poor clinical outcomes in OC patients. We proved that HEY-T30 cells overexpress CSC markers and much more invasive than other cancer cells. Flow cytometry (FACS) and microscopic analysis revealed the active targeting property of PheoA-SN38-HC NPs to CD44+ HEY-T30 cells. Moreover, the combination therapeutic effect of PheoA-SN38-HC NPs was clearly demonstrated against in vitro HEY-T30 cells and an in vivo xenograft mouse model. In particular, the paracrine cytotoxic effect of SN38 probably compensates the locoregional therapeutic limitation of photodynamic therapy. Graphical abstract: Here, we prepare combination therapeutic hyaluronan nanoparticles conjugated with photodynamic pheophorbide A and ROS-cleavable thioketal-SN38. Based on CPTAC data, HEY-T30 human ovarian cancer cells with high expression of cancer stem cell (CSC) markers (AHLD1A1, CD44 and CD117) is selected for cancer model. Pan-CSC marker targeting using CD44-specific and combination-designed nanoparticles proposes therapeutic potentials for overcoming refractory ovarian cancers. Unlabelled Image Highlights: We design CD44 targeting NPs conjugated with pheophorbide A and ROS-cleavable SN38. Photodynamic ROS and release of SN38 demonstrate combination therapeutic efficacy. We observe chemo-resistant HEY-T30 cells overexpress cancer stem cell markers. Paracrine release of SN38 compensates for the light-confined local effect of PDT.